Thromboinflammatory complications of Bothrops snakebite envenoming: the case of B. lanceolatus endemic to the Caribbean Island of Martinique - Rapon, Caroline; Florentin, Jonathan; Radouani, Fatima; Jalta, Prisca; Negrello, Florian; Gueye, Papa; Pierre-Louis, Olivier; Neviere, Remi; Resiere, Dabor (Frontiers in Immunology, 2025)
Snakebite envenoming remains a predominant neglected disease in tropical and subtropical regions, with high rates of morbidity and mortality worldwide. Bothrops snakebite envenoming. is characterized by severe injuries at the site of venom injection, which include tissue necrosis, hemorrhage, blistering, and edema. Haemotoxicity is typically attributed to the strong procoagulant state induced by the majority Bothrops venoms leading to coagulation factor consumption and incoagulable blood. Concomitantly with this procoagulant state, a complex host response develops in the affected tissues, accompanied by the recruitment of inflammatory and immunocompetent cells, along with the activation of resident cells, and the synthesis of a plethora of pro-inflammatory mediators and damage-associated molecular patterns from injured tissue. An increasing body of evidence suggests that this intricate response is, in fact, related to the well-documented immunothrombosis and thromboinflammation integrated features. Of note, thrombotic complications are extremely rare in Bothrops snakebite envenoming. However, in the case of Bothrops lanceolatus and B. caribbaeus, which are respectively endemic to Martinique and St. Lucia, the absence of overt consumption coagulopathy due to their weak procoagulant effects may be related to the thrombotic effects, as clotting factors are present in the bloodstream by the time the thrombogenic and inflammatory mechanisms are operating in blood vessels. Prior to the era of immunotherapy, B. lanceolatus envenoming was associated with thrombotic complications in 25% of cases and was fatal in approximately 10% of cases. This review examines the potential role of thromboinflammation as a mechanism of thrombotic accidents in B. lanceolatus snakebite envenoming.